Endovascular management of renal artery aneurysms using the multilayer flow modulator. Issue 1 (10th March 2016) - Sultan, Sherif; Basuoniy Alawy, Mahmoud; Flaherty, Rita; Kavanagh, Edel P; Elsherif, Mohamed; Elhelali, Ala; Stefanov, Florian; Lundon, Violet; Hynes, Niamh
Abstract : Objective: Our aim was to describe our experience of the Multilayer Flow Modulator (MFM, Cardiatis, Isnes, Belgium) used in the treatment of type III renal artery aneurysms (RAA). Methods: This is a single-centre study. 3 patients (2 men and 1 woman; mean age 59 years; range 41–77 years) underwent treatment of a type III renal artery aneurysm using the MFM. The indications were a 23.9 mm type III RAA at the bifurcation of the upper and lower pole vessels, with 4 side branches; a 42.4 mm type III saccular RAA at the renal hilum; and a 23 mm type III RAA at the origin of the artery, supplying the upper pole. Results: Patients had a mean follow-up of 27 months, and were assessed by perioperative renal function tests, and repeat postoperative CT scan. There were no immediate postoperative complications or mortality. The first patient's aneurysm shrank by 8.6 mm, from 23.9 to 15.3 mm over 19 months, with all 4 side branches remaining patent. The largest aneurysm at 42.4 mm completely thrombosed, while the renal artery remained patent to the kidney. The final patient refused to have any follow-up scans but had no deterioration in renal function below 30 mL/min, and no further symptoms reported. Conclusions: The MFM is safe and effective in the management of patients with complex renal artery aneurysms. The MFM can be used to treat branched or distal renal artery aneurysms with exclusion of the aneurysm from the circulation, while successfully preserving the flow to the side branches and kidney. Initial results are promising, however, longer follow-up and a larger cohort are required to prove the effectiveness of this emerging technology.